BOARDING SCHOOL DAN PEMBENTUKAN KARAKTER SISWA: ANALISIS HUMANISTIK DI SMPIT DARUL FIKRI MAKASSAR - Sulfajri; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the formation of student character through a humanistic approach in the boarding school environment at SMPIT Darul Fikri Makassar. The research used a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving teachers, dormitory supervisors, and students. The results showed that the humanistic approach implemented through exemplary behavior, emotional support, open communication, and positive habituation played an important role in shaping students’ character. The findings indicated improvements in students’ independence, responsibility, discipline, empathy, integrity, and manners. In addition, the supportive boarding school environment, structured routines, and collaboration between the school and parents became important factors in strengthening character development. The study concludes that a humanistic approach in the boarding school environment can help students internalize character values consciously and apply them in daily life.